Child development in an ideological context: Through the lens of resistance and accommodation. (6th November 2021) - Rogers, Leoandra Onnie; Way, Niobe
Abstract: Every aspect of child development—from cognition to relationships—is shaped by macrolevel ideologies (e.g., white supremacy, patriarchy) that reflect the social hierarchies and embedded power structures of society. While ecological theories have long underscored the impact of macrosystems and cultures on humans, the field of child development has tended to overemphasize microsystems and often overlooks how ideologies of power shape developmental processes. In this article, we situate child development within and in response to the ideological context, which directs the field's attention away from "fixing" individuals and microsystems and toward disrupting the macro‐ideologies that shape them. We ground this article in research on resistance and accommodation to such ideologies, revealing that humans have a natural capacity to resist what gets in the way of their ability to survive and thrive. We discuss questions that are necessary to address when integrating resistance and accommodation in the study of child development.